Influence of Family Economic Status on Education and Health of Special Children in Islamabad - Lubna Faraz; Hina Noor; Qaisara Parveen (JIE, 2018)
The study was conducted to find out the economic status of the parents of special children residing in Islamabad and its influence on their health and academic condition. The population of the study comprised the children with special needs studying in grade 1-10 in 4 model government special education institutions in Islamabad. The sample of 10 special children from each grade was randomly selected. A questionnaire was developed for classifying the parents with special children into poor, middle class and well off. The questionnaire was developed for teachers to obtain information regarding academic status of the special children. The medical case history forms and the observation checklist were used to assess the health condition of the sample. The data collected through the questionnaire were tabulated and analyzed using descriptive and inferential statistics via SPSS. A strong correlation was obtained between socioeconomic status and health conditions as well as academic status of these children. Multiple comparison analysis revealed the significant difference in academic status of the children belonging to very poor and the high income group. But no significant difference was found between health conditions of the children with special needs belonging to different socio-economic status.